POTENSI WISATA BUDAYA BENTENG BOMBONAWULU KECAMATAN GU KABUPATEN BUTON TENGAH - Said, Nurzalma Alfianti; Niampe, La; Marhadi, Akhmad (Jurnal Penelitian Budaya, 2021)
The purpose of this study is to describe and analyze the potential for historical tourism and cultural tourism in Fort Bombonawulu. The theory used in this study refers to the concept of sustainable tourism by Muller, namely 5 things that must be considered, including: healthy economic growth, the welfare of local communities, not changing natural structures and protecting natural resources, community culture that grows healthily and maximizes satisfaction. traveler. The method used in this research is qualitative research methods. Data collection techniques in this study were observation, interviews, documentation study, and triangulation of data sources. The research data was studied using qualitative descriptive techniques. The results of the analysis in this study indicate that Fort Bombonawulu has tourism potential both historical tourism marked by the presence of several ancient tombs (kobuhu), mosques (masigi), flags (tombi), galampa daduwali, lawa and also bastion, and cultural tourism which includes several events such as the bongkaa tau cultural festival, the kakadhiuno bukuno kamokulano liwu ritual, and the kadhiuno liwu / kabhiano liwu ritual which presents cultural attractions such as linda mboreranga, mangaru, pokalapa, kabhanti gambusu, andoro-andoro, latotou, as well as traditional culinary that can attract many visitors or traveler. The bombonawulu fort site has the potential for cultural history tourism, both tangible and intangible.Keywords: Fort Bombonawulu, culture, culinary, tourism, history.